(untitled) (Acta Scientiarum. Technology, 2013)
The enzyme cyclomaltodextrin-glucanotransferase (CGTase) is a transglicosidase able to convert corn starch into cyclodextrin (CD). CDs are widely applied in industry given the ability to form inclusion complexes with a great variety of organic molecules. Regarding the optimum pH of CGTase, values reported in the literature vary according to the enzyme producing microorganism, being 8.0 the optimum pH of CGTase produced by Bacillus firmus Strain No. 37. This work studied the influence of the pH of culture medium with different concentration of nutrients on the production of the enzyme CGTase by Bacillus firmus Strain No. 37. For this purpose, the microorganism was grown in three culture media with different concentrations of carbon and nitrogen. The pH control was performed by adding sodium carbonate. The fermentation process was analyzed by the following methods: Bradford (1976) method to determine soluble proteins, DNS method to analyze sugars, and the method of complexation with Î²-CD to analyze the enzyme activity. The best result for CGTase enzyme activity was 0.22 U mL-1, obtained with medium containing 2.0% soluble corn starch and yeast extract, and pH 8.3.